Gender Inequality and Growth : The Case of Rich vs. Poor Countries - Amin, Mohammad; Kuntchev, Veselin; Schmidt, Martin (World Bank Group, Washington, DC, 2015)
This paper uses cross-section data for 107 countries to explore the relationship between gender inequality and economic growth. The paper departs from the literature by using a broad measure of gender inequality that goes well beyond gender inequality in education, which has been the focus of most studies. Another novelty of the paper lies in exploring heterogeneity in the growth-gender inequality relationship. The results confirm that greater gender inequality is strongly associated with lower economic growth. However, this negative relationship between gender inequality and growth is entirely due to the relatively poor countries, with the relatively rich countries showing no such relationship. The findings have important implications for the design and targeting of gender-specific policies.